GESTIÓN DE RIESGOS DEL PATRIMONIO CULTURAL: ALCANCES PARA EL PATRIMONIO HISTÓRICO INMUEBLE - Santander Cjuno, Clary Diana (2017)
This article connects basic concepts to heritage management and risk management of cultural heri- tage. Thus, to tackle this subject, it starts with a picture of the concepts of cultural heritage, since the theory about it is dynamic, changing, and very important for contemporary society. In order to ad- dress the central topic, concepts related to risks, cultural heritage and their management have been employed, to then integrate them with greater detail to the approach studied here. Finally, the most relevant aspects of the methodology developed by the Canadian Conservation Institute (ICC), the International Center for the Study of the Preservation and Restoration of Cultural Property (ICCROM) and the Cultural Heritage Agency of the Netherlands (RCE) have been included. Risk management encompasses the evaluation, analysis, proposals, plans and other aspects related to the practice of a public/private organization in order to minimize risk when decision making about cultural heritage management occurs.